Transgenerational exposure to marine heatwaves ameliorates the lethal effect on tropical copepods regardless of predation stress. Issue 8 (4th August 2022) - Truong, Kiem N.; Vu, Ngoc‐Anh; Doan, Nam X.; Bui, Canh V.; Le, Minh‐Hoang; Vu, Minh T. T.; Dinh, Khuong V.
Abstract: Marine heatwaves (MHWs) are emerging as a severe stressor in marine ecosystems. Extreme warm sea surface temperatures during MHWs often exceed the optimal thermal range for more than one generation of tropical coastal zooplankton. However, it is relatively unknown whether transgenerational plasticity (TGP) to MHWs may shape the offspring's fitness, particularly in an ecologically relevant context with biotic interactions such as predation stress. We addressed these novel research questions by determining the survival, reproductive success, and grazing rate of the copepod Pseudodiaptomus incisus exposed to MHW and fish predator cues (FPC) for two generations (F1 and F2). The experiment was designed in a full orthogonal manner with 4 treatments in F1 and 16 treatments in F2 generation. In both generations, MHW reduced P. incisus survival, reproductive parameters, and grazing by 10%–62% in MHW, but these parameters increased by 2%–15% with exposure to FPC, particularly at control temperature. F2 reproductive success and grazing rate as indicated by cumulative fecal pellets were reduced by 20%–30% in F1‐MHW, but increased by ~2% in F1‐FPC. Strikingly, MHW exposure reduced 17%–18% survival, but transgenerational exposure to MHWs fully ameliorated its lethal effect and this transgenerational effect was independent of FPC. Increased survival came with a cost of reduced reproductive success, constrained by reduced grazing. The rapid transgenerational MHW acclimation and its associated costs are likely widespread and crucial mechanisms underlying the resilience of coastal tropical zooplankton to MHWs in tropical coastal marine ecosystems. Abstract : Marine heatwaves emerge as a severe stressor in marine ecosystems, yet it is relatively unknown whether transgenerational effect of marine heatwaves may shape the offspring fitness, particularly in an ecologically relevant context with biotic interactions such as predation stress. Our study showed that transgenerational exposure to marine heatwaves fully ameliorated its lethal effect on tropical copepod Pseudiaptomus incisus with a cost of reduced reproductive success constrained by the lowered grazing. Fish predation stress played a minor role in shaping the copepod performance, both within and across generations with or without marine heatwaves.